2017
DOI: 10.1080/02699052.2017.1285051
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cognitive and neuroanatomical stability in patients with anoxic amnesia: A Case Report

Abstract: Patients with an amnesia due to anoxia have memory impairments and smaller hippocampal volumes compared to controls; however, memory, intelligence and structural volumes remain stable over time. At ages 50 and 57, they do not appear to have early age-associated cognitive decline that is sometimes observed in patients with traumatic brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Research on hypoxic/anoxic brain injury associated with strangulation in IPV is growing, and evidence from past work in cardiac arrest, non-fatal drowning, and sleep apnea indicate that anoxic/hypoxic injuries are associated with impaired memory, processing speed, attention, as well as executive dysfunction (Anderson & Arciniegas, 2010;Bichard, Byrne, Saville, & Coetzer, 2020;Caine & Watson, 2000;Monahan, Purushotham, & Biegon, 2019;Peskine, Rosso, Picq, Caron, & Pradat-Diehl, 2010;Wright, Kirwan, Gale, Levan, & Hopkins, 2017). In addition, studies of self-reported symptoms after strangulation show a high frequency of neurological symptoms such as dizziness, loss of consciousness, loss of sensation, and memory problems (Smith, Mills, & Taliaferro, 2001;Wilbur et al, 2001), with some evidence that the frequency of symptoms increases with the instances of strangulation (Smith et al, 2001).…”
Section: Neurocognitive Outcomes: Cognitive Impairment In Ipv Ipv-rementioning
confidence: 99%
“…Research on hypoxic/anoxic brain injury associated with strangulation in IPV is growing, and evidence from past work in cardiac arrest, non-fatal drowning, and sleep apnea indicate that anoxic/hypoxic injuries are associated with impaired memory, processing speed, attention, as well as executive dysfunction (Anderson & Arciniegas, 2010;Bichard, Byrne, Saville, & Coetzer, 2020;Caine & Watson, 2000;Monahan, Purushotham, & Biegon, 2019;Peskine, Rosso, Picq, Caron, & Pradat-Diehl, 2010;Wright, Kirwan, Gale, Levan, & Hopkins, 2017). In addition, studies of self-reported symptoms after strangulation show a high frequency of neurological symptoms such as dizziness, loss of consciousness, loss of sensation, and memory problems (Smith, Mills, & Taliaferro, 2001;Wilbur et al, 2001), with some evidence that the frequency of symptoms increases with the instances of strangulation (Smith et al, 2001).…”
Section: Neurocognitive Outcomes: Cognitive Impairment In Ipv Ipv-rementioning
confidence: 99%